Driving Factors of Rural Land-Use Change from a Multi-Scale Perspective: A Case Study of the Loess Plateau in China - Bo Hu; Qingsong Ni; Zongfeng Chen; Xueqi Liu; Pingan Liu; Ziyi Yuan (Land)
The issue of multi-scale driving forces within land systems has emerged as one of the pivotal research directions for innovative exploration in the field of land science. However, the understanding of the differences in driving factors across different scales remains relatively inadequate. Based on multi-source data spanning from 2000 to 2020, this study applied GeoDetector models to reveal the evolution of the spatiotemporal pattern of land-use change and the scale differences in driving factors in rural areas of the Loess Plateau region from both prefecture-level scale and township scale. The results indicated that the land-use changes in rural areas of the Loess Plateau had exhibited distinct spatial differentiation characteristics over the past 20 years. Specifically, the land-use change dynamic degree on the Loess Plateau exhibits an upward trend from west to east (slope = 0.031) and a downward trend from north to south (slope = −0.039). Secondly, the spatial scale differences in driving forces of rural land-use change in the Loess Plateau were manifested through variations in dominant factors and differences in the sensitivity of land-use change to various factors. The reasons for these differences lay in scale effects and cumulative effects. These findings would provide decision-making support for policymakers in formulating future sustainable land-use policies for rural areas. Additionally, it would contribute to further advancing the exploration of multi-scale driving forces within rural land systems.